Perlindungan Konsumen Terhadap Suntik Battery Health Pada Jual Beli Iphone Second Original Perspektif Wahbah Az Zuhaili: Studi Kasus di Kecamatan Banda Sakti, Kota Lhokseumawe - Nidar Maulana; Rahmat Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study discusses consumer protection against the practice of battery health injection in the sale of original second-hand iPhones in Banda Sakti District, Lhokseumawe City, in the perspective of Wahbah Az-Zuhaili. The practice of battery health injection is the process of manipulating iPhone battery health data to appear higher than the actual condition, this action is often carried out by unscrupulous sellers to increase the selling price of the device. This has the potential to harm consumers because the information provided does not correspond to the actual physical condition. This study aims to determine the form of legal protection for consumers and assess the truth of this practice from the perspective of Islamic law according to the thoughts of Wahbah Az-Zuhaili. The research method used is an empirical research type with a legislative approach, a conceptual approach, a case study approach and data collection techniques in the form of interviews and observations of sellers and buyers in the research area.. The results of the study indicate that the practice of battery health injection is included in the category of tadlis (fraud) in the form of aib (defect) which is prohibited in Islam, and is contrary to the principles of honesty and openness in selling transactions according to Wahbah Az-Zuhaili. Therefore, stricter rules and guidance are needed to protect consumer rights, both in positive law and Islamic law.